2020
DOI: 10.1038/s41598-020-67089-0
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific expression is widespread in Bos indicus muscle and affects meat quality candidate genes

Abstract: Differences between the expression of the two alleles of a gene are known as allele-specific expression (ASE), a common event in the transcriptome of mammals. Despite ASE being a source of phenotypic variation, its occurrence and effects on genetic prediction of economically relevant traits are still unexplored in bovines. Furthermore, as ASE events are likely driven by cis-regulatory mutations, scanning them throughout the bovine genome represents a significant step to elucidate the mechanisms underlying gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Two ASE SNPs described by Guillocheau et al (2019) were identified here as aseQTLs: rs109170993, associated with the rs110850310 ASE SNP, and rs109842586, associated with the rs109372848 ASE SNP. The rs109842586 was also identified marking ASE in our population as well 5 .…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…Two ASE SNPs described by Guillocheau et al (2019) were identified here as aseQTLs: rs109170993, associated with the rs110850310 ASE SNP, and rs109842586, associated with the rs109372848 ASE SNP. The rs109842586 was also identified marking ASE in our population as well 5 .…”
Section: Discussionmentioning
confidence: 51%
“…Additionally, CMYA5 had 245 overlaps between aseQTLs and QTLs for b*FAT, CL, L*FAT, REA, WBSF0, WBSF7, and WHC traits. In addition, ASE genes in the bovine muscle functionally enriched for meat quality traits were previously identified in our population 5 and elsewhere 8 . Although these overlaps with QTLs might be useful for prioritizing SNPs for validation, a word of caution is necessary, as the confidence intervals for the QTLs might be considerable and could not be taken into account in our analyzes.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations